CAUSE OF CONFLICT BETWEEN TWO INDIGENOUS CHARACTER AS THE IMPACT OF BRITISH IMPERIALISM IN ORWELL’S BURMESE DAYS - Nur Afiah (JOEL: Journal of Educational and Language Research, 2021)
This study aims to outline the cause of conflict between two indigenous chatacter in Orwell’s Burmese Days. During the process of its creation, the writer believes that this novel is created as a response from the author to the social phenomenon at that period. Qualitative is used in this study and genetic structuralism by Lucien Goldmann is the theory which will be applied. The main sorce of this study is collecting the description and utterances of the characters and the narrator. The result of this study indicates that the main conflict between two indigenous is caused by the new regulation of the English Men by announcing that they will accept on an indigenous to be a member of European Club. European Club portrays as the spiritual citadel, the real seat of the British power, the Nirvana for which native officials and millionaires pine in vain. By joining this Club, the indigenous self-regard will be the same as well as the English Men. An nalysis of the cause of conflict between two indigenous is the main object of this research, it is suggested to other writersto analyze other aspects in Orwell's Burmese Days, such as: social inequality, gender, obedience, racism, and other social aspects.